Unified approach to fused and spirocyclic oxindoles through lewis-acid-promoted opening of spiroepoxyoxindoles with allylsilanes: application to the formal synthesis of (+/-)-physovenine - Sharma, Brijesh M.; Yadav, Mahesh; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2017)
A protocol for the construction of oxindoles containing all-carbon quaternary centres in a highly regioselective manner has been developed. The reaction involves opening of spiroepoxyoxindoles with allylsilanes to give Hosomi-Sakurai-type products as well as new silicon-containing spirocyclic oxindoles. A formal synthesis of (+/-)-physovenine was accomplished in five steps using this protocol.
Keywords: alkaloids; Allylation; annulation; Lewis acids; spiro compounds

Unravelling the nucleophilicity of buten tides for 1,6-conjugate addition to p-quinone methides: a direct access to diversely substituted butenolide-derived diarylmethanes - Sharma, Brijesh M.; Shinde, Dinesh R.; Jain, Ruchi; Begari, Eeshwaraiah; Satbhaiya, Shruti; Gonnade, Rajesh G.; Kumar, Pradeep (Organic Letters, 2018)
A Lewis acid catalyzed regioselective C-C bond is constructed through beta-addition of deconjugated butenolides with p-quinone methides in a 1,6-conjugate addition manner. Interestingly, Lewis acid catalyzed vinylogous Mukaiyama-Michael reaction of silyloxyfurans with p-QMs proceeds selectively through the alpha or gamma position exclusively. The reaction is mild with broad substrate scope, thus allowing easy access to a wide range of bis-arylated alpha-/beta-/gamma-substituted butenolides.